5-year overall survival in patients with lung cancer eligible or ineligible for screening according to US Preventive Services Task Force criteria: a prospective, observational cohort study. Issue 8 (August 2019) - Luo, Yung-Hung; Luo, Lei; Wampfler, Jason A; Wang, Yi; Liu, Dan; Chen, Yuh-Min; Adjei, Alex A; Midthun, David E; Yang, Ping
Summary: Background: The US Preventive Services Task Force (USPSTF) recommends lung cancer screening among individuals aged 55–80 years with a 30 pack-year cigarette smoking history and, if they are former smokers, those who quit within the past 15 years. Our previous report found that two-thirds of newly diagnosed patients with lung cancer do not meet these criteria; they are reported to be either long-term quitters (≥15 years since quitting) or from a younger age group (age 50–54 years). We aimed to assess survival outcomes in these two subgroups. Methods: For this prospective, observational cohort study we identified and followed up patients aged 50–80 years with lung cancer, with a smoking history of 30 pack-years or more, and included both current smokers and former smokers who quit within the past 30 years. We identified patients from two cohorts in the USA: a hospital cohort (Mayo Clinic, Rochester, MN) and a community cohort (Olmsted County, MN). Patients were divided into those meeting USPSTF criteria (USPSTF group) versus those not meeting USPSTF criteria (long-term quitters or the younger age group). The main outcome was overall survival at 5 years after diagnosis. 5-year overall survival was analysed with and without matching age and pack-years smoked for long-term quitters. The USPSTF group was subdivided into two age subgroups (55–69 years and 70–80 years) for multivariable regression analysis. Findings: Between Jan 1, 1997, and Dec 31, 2017, 8739 patients with lung cancer were identified and followed up. Median follow-up was 6·5 (IQR 3·8–10·0) years, and median overall survival was 16·9 months (95% CI 16·2–17·5). 5-year overall survival was 27% (95% CI 25–30) in long-term quitters, 22% (19–25) in the younger age group, and 23% (22–24) in the USPSTF group. In both cohorts, 5-year overall survival did not differ significantly between long-term quitters and the USPSTF group (hospital cohort: hazard ratio [HR] 1·02 [95% CI 0·94–1·10]; p=0·72; community cohort: 0·97 [0·75–1·26]; p=0·82); matched analysis showed similar results in both cohorts. 5-year overall survival also did not differ significantly between the younger age group and the USPSTF group in both cohorts (hospital cohort: HR 1·16 [95% CI 0·98–1·38], p=0·08; community cohort: 1·16 [0·74–1·82]; p=0·52); multivariable regression analyses stratified by age group yielded similar findings. Interpretation: Patients with lung cancer who quit 15 or more years before diagnosis and those who are up to 5 years younger than the age cutoff recommended for screening, but otherwise meet USPSTF criteria, have a similar risk of death to those individuals who meet all USPSTF criteria. Individuals in both subgroups could benefit from screening, as expansion of USPSTF screening criteria to include these subgroups could enable earlier detection of lung cancer and improved survival outcomes. Funding: National Institutes of Health and the Mayo Clinic Foundation.